2015
DOI: 10.1177/0040517515569523
|View full text |Cite
|
Sign up to set email alerts
|

Delicate laundering of textiles with application of 38 kHz ultrasonic waves

Abstract: Ultrasonic cleaning in aqueous solutions was performed using various plain-woven fabrics soiled with oleic acid and/or carbon black as model oily and particulate contaminants. Detergency, which was evaluated from the change in the surface reflectance of the soiled fabrics due to cleaning, was promoted by applying ultrasound as the mechanical action for soil removal in the absence and the presence of anionic surfactant. Both soils were removed easily from the filament fabrics compared with the spun fabrics. Ult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…[10][11][12][13][14][15][16][17] Ultrasound can improve laundering efficiency by achieving good stain removal whilst maintaining the quality of delicate fabric, which may be disrupted by mechanical washing. 20,21 In bleaching, it was shown that ultrasonic pretreatment of wool can increase the effectiveness of the oxidative-reductive process. 22 Acoustic cavitation is considered responsible for most of the ultrasound physical and chemical effects observed in solid/liquid or liquid/liquid systems.…”
mentioning
confidence: 99%
“…[10][11][12][13][14][15][16][17] Ultrasound can improve laundering efficiency by achieving good stain removal whilst maintaining the quality of delicate fabric, which may be disrupted by mechanical washing. 20,21 In bleaching, it was shown that ultrasonic pretreatment of wool can increase the effectiveness of the oxidative-reductive process. 22 Acoustic cavitation is considered responsible for most of the ultrasound physical and chemical effects observed in solid/liquid or liquid/liquid systems.…”
mentioning
confidence: 99%
“…Washing of clothing in domestic laundering machines is infl uenced by physicochemical and mechanical actions. The physicochemical action plays a role in separating soil from clothes and dispersing it into the detergent solution, whereas the mechanical action facilitates separating soil from textiles by fl exing and inducing friction between textiles, moving loosened soil to the detergent solution, and delivering fresh detergent solution to the textile surfaces [1][2][3][4]. Based on the classifi cation of the mechanical actions of washing (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Mechanical action can separate soils by inducing flexing and friction between fabrics, moving separated soils to detergent solution, and delivering fresh detergent solution to textile surfaces. 2,3 Therefore, a balanced understanding of both physicochemical and mechanical actions is necessary to precisely control washing mechanisms and improve detergency. 4 However, earlier studies on textile washing have mainly focused on physicochemical factors, such as soil type, water quality, detergent composition, and washing temperature.…”
mentioning
confidence: 99%